Stress-Strain Calculation Method of Composite Lining considering the Creep Characteristics of Tunnel Surrounding Rock - Shuancheng Gu; Hengwei He; Rongbin Huang (Advances in Civil Engineering)
Tunnels are generally designed for a sustained usage of 80 to 100 years, during which the safety of tunnel structures must be guaranteed. A common supporting form utilized in contemporary tunnel engineering is composite lining. To derive applicable parameters of the supporting form and therefore ensure the long-term safety of the tunnel structure, it is imperative to determine the extra acting force exerted onto the composite lining by the creep of the rock surrounding the tunnel and to calculate the stress-strain characteristics of composite lining. In the current study, this paper proposes an approach termed surrounding reinforcement, which is based on the homogenization method. Specifically, this paper defined the bolt force as the internal force of the surrounding rock, analyzed their viscoelastic-plastic properties using the unified strength theory, and derived an equation for calculating the stress-strain relationship of the composite lining. To further validate the method in tunnel structures, this paper applied the derived equation to a representative instance. The results of this paper show that the initial support force has also increased during the creep process of the surrounding rock, indicating that engineers should pay close attention to the coordination between the strength of initial support and the secondary lining and thus ensure an optimal distribution of the pressure from the surrounding rock when designing composite lining tunnel within weak strata. This paper proposes that the initial support not only would guarantee the tunnel safety during the construction stage but also could cooperate with the secondary lining to brace the stress caused by the creep, ensuring that the supporting structure stays stable across the whole period of tunnel operation. This paper provides an alternative to previous methods that is more comprehensive, with simpler calculations, and more applicable to the composite lining supporting design within weak strata.